Constructivism Paradigm in Islamic Religious Education - Asiana Asiana; Ismarani Junia Putri; Muhammad Irsyad Saifullah; Indah Wigati; Fitri Ovi Yanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The constructivist paradigm within Islamic Religious Education (PAI) highlights the students' active involvement in forming knowledge through their experiences, reflection, and social interactions. This research employs a qualitative descriptive method, using a literature review approach to examine the integration of constructivism in PAI learning. Findings indicate that the constructivist approach leads PAI education towards a more participatory, contextual, and human-centered path. Students are transformed from passive recipients of information to active creators of meaning through critical and reflective thinking. Teachers take on roles as facilitators and mediators, aiding students in linking religious concepts to everyday reality. This paradigm also aligns with the evolution of new literacies, such as digital, data, and humanistic literacy, required in today’s world, enabling students to assess religious information critically and responsibly. Hence, constructivism in PAI serves as a conduit between traditional Islamic values and the demands of modern education, fostering individuals who are intellectually, spiritually, and socially adept.